BBS5 and INPP5E mutations associated with ciliopathy disorders in families from Pakistan. (7th June 2019) - Khan, Shazia; Lin, Siying; Harlalka, Gaurav V.; Ullah, Asmat; Shah, Khadim; Khalid, Sumbul; Mehmood, Sarmad; Hassan, Muhammad Jawad; Ahmad, Wasim; Self, Jay E.; Crosby, Andrew H.; Baple, Emma L.; et al.
Abstract: Ciliopathies are a clinically and genetically heterogeneous group of disorders often exhibiting phenotypic overlap and caused by abnormalities in the structure or function of cellular cilia. As such, a precise molecular diagnosis is important for guiding clinical management and genetic counseling. In the present study, two Pakistani families comprising individuals with overlapping clinical features suggestive of a ciliopathy syndrome, including intellectual disability, obesity, congenital retinal dystrophy, and hypogonadism (in males), were investigated clinically and genetically. Whole‐exome sequencing identified the likely causes of disease as a novel homozygous frameshift mutation (NM_152384.2: c.196delA; p.(Arg66Glufs*12); family 1) in BBS5, and a nonsense mutation (NM_019892.5:c.1879C>T; p.Gln627*; family 2) in INPP5E, previously reported in an extended Pakistani family with MORM syndrome. Our findings expand the molecular spectrum associated with BBS5 mutations in Pakistan and provide further supportive evidence that the INPP5E mutation is a common cause of ciliopathy in Northern Pakistan, likely representing a regional founder mutation. This study also highlights the value of genomic studies in Pakistan for families affected by rare heterogeneous developmental disorders and where clinical phenotyping may be limited by geographical and financial constraints. The identification of the spectrum and frequency of disease‐causing variants within this setting enables the development of population‐specific genetic testing strategies targeting variants common to the local population and improving health care outcomes.